548Cancer treatment and survival disparity in South Australia women with invasive breast cancer during 2000-2014. (2nd September 2021) - Li, Ming; Roder, David
Abstract: Background: Survival improvement from breast cancer has been attributed mostly to treatment advances and earlier cancer detection. This study was to investigate cancer treatment and the association with survival. Methods: A total of 13494 female patients with invasive breast cancer recorded on the South Australia Cancer Registry in 2000-2014 were included. Cancer treatments within 12 month following diagnosis were identified from linked cancer registry and other medical registries. Study factors included demo sociographic, tumour profile and comorbidity. Adjusted odds ratios and sub hazard ratios were reported on treatment and survival disparity respectively. Results: 98% patients were treated with one or more treatment types. 56% had conserving surgery. Systemic treatment was received by 72%. Older patients with advanced cancer were less likely to have any treatment. Women in the most socioeconomically advantaged area were less likely to have combined mastectomy and conservative surgery (aOR 0.73, 95% CI 0.54-0.98), but more likely to have systemic treatment (aOR 1.44, 95% CI 1.26-1.64). Other factors such as country of birth, residential socioeconomic status, cancer differentiation, and diagnosis period differed in their associations with treatment type. Having conserving surgery predicted the lowest breast cancer death (adjusted SHR 0.31, 95% CI 0.26-0.36) compared to no surgery. Conclusions: Breast cancer patients underwent varied treatment types with different impact on breast cancer mortality. Key messages: Patients undergoing conserving surgery were at the lowest risk of the cancer death.